(untitled) (Islas, 2022)
ABSTRACT Introduction: This work aims to assess the possibilities of reading and its promotion for the transformation of complex communities. Methods: The inductive-deductive method and the bibliographic review were applied to systematize what refers to the work with the promotion of reading in complex communities. Results: The work with the promotion of reading has limitations of pedagogically based proposals that serve as references for making methodological decisions about the promotion of reading in the communities, with emphasis on the so-called complex ones due to their extra-urban location, population density, low cultural level and functional illiteracy. Conclusions: Reading is not a passive act, but rather requires the reader to put into function a series of mental structures that develop with this process (intelligence, analysis, reasoning, among other).